2000
DOI: 10.1055/s-0037-1613802
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mouse Thrombin-activatable Fibrinolysis Inhibitor

Abstract: SummaryBased on in vitro studies, thrombin-activatable fibrinolysis inhibitor (TAFI) has been hypothesized as a link between coagulation and fibrinolysis, but the physiological role of TAFI in vivo has not yet been established. To anticipate on the availability of genetically modified mouse models, we studied the endogenous expression of TAFI in mice. Functional TAFI was found in mouse plasma. TAFI mRNA was only detectable in the liver, showing a hepatocyte-specific expression with a pericentral lobular distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…Currently, studies are underway to address these issues. During the preparation of our manuscript, Wagenaar et al independently reported generation of TAFI-deficient mice and observed a lack of abnormal phenotypes in their TAFI-deficient mice, consistent with our result (65).…”
Section: Figuresupporting
confidence: 91%
“…Currently, studies are underway to address these issues. During the preparation of our manuscript, Wagenaar et al independently reported generation of TAFI-deficient mice and observed a lack of abnormal phenotypes in their TAFI-deficient mice, consistent with our result (65).…”
Section: Figuresupporting
confidence: 91%